2020
DOI: 10.1088/1361-6463/ab678f
|View full text |Cite
|
Sign up to set email alerts
|

High linearity and high power performance with barrier layer of sandwich structure and Al0.05GaN back barrier for X-band application

Abstract: The high power and linearity performance of GaN-based HEMT for X-band application was achieved using the barrier layer of sandwich structure and Al0.05GaN back barrier. The AlGaN-sandwich-barrier can modulate polarization-graded field for more flat transconductance profile under the high drain bias. Only about 7.5% current collapse (CC) occurs for drain quiescent bias of 40 V. Due to the Al0.05GaN back barrier, the three-terminal off-state breakdown voltage (BVDS) of 260 V and a very small drain-induced barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Jeong-sun Moon et al [160] used AlGaN/GaN graded channel which have good PAE and linearity. Bin Hou et al [161] used barrier layer of sandwich structure and AlGaN back barrier which show good power performance and linearity. Kai Zhang et al [162] used Fin-FET HEMT that have good linearity compared to the planar HEMT.…”
Section: Rf Gan Performance Si Substratementioning
confidence: 99%
“…Jeong-sun Moon et al [160] used AlGaN/GaN graded channel which have good PAE and linearity. Bin Hou et al [161] used barrier layer of sandwich structure and AlGaN back barrier which show good power performance and linearity. Kai Zhang et al [162] used Fin-FET HEMT that have good linearity compared to the planar HEMT.…”
Section: Rf Gan Performance Si Substratementioning
confidence: 99%
“…Bajaj et al [11] [12] have demonstrated graded AlGaN channel PolFETs in which spreading the polarization charge across the graded AlGaN layers in a 3D space results in a distributed electron density and renders a constant ν sat as a function of gate bias. This significantly suppresses the higher order harmonics and improves the linearity of the device [13].…”
Section: Introductionmentioning
confidence: 99%
“…for 5G radio frequency (RF) front-end modules such as microwave monolithic integrated circuit power amplifiers [1][2][3][4]. The current commercial RF devices based on AlGaN/GaN high electron mobility transistors (HEMTs) are usually grown on SiC substrates, whereby the small-size and expensive SiC substrate cost has hampered their larger-scale deployment for cost-sensitive applications, such as mobile phones.…”
Section: Introductionmentioning
confidence: 99%